Glutamate in Salience Network Predicts BOLD Response in Default Mode Network During Salience Processing - von Düring, Felicia; Ristow, Inka; Li, Meng; Denzel, Dominik; Colic, Lejla; Demenescu, Liliana Ramona; Li, Shijia; Borchardt, Viola; Liebe, Thomas; Vogel, Matthias; Walter, Martin (Frontiers in Behavioral Neuroscience, 2019)
Background: Brain investigations identified a salience network (SN) comprising the dorsal Anterior Cingulate Cortex (dACC) and the Anterior Insula. Magnetic resonance spectroscopy (MRS) studies revealed the link between glutamate concentration in ACC and alterations in attentional scope. Hence, we investigated whether glutamate concentration in the dACC modulates brain response during salience processing. Methods: Glutamate concentrations in dACC were measured in thirty-one healthy subjects (14♀, 17♂) using STEAM MRS at 7T, followed by a functional magnetic resonance imaging (fMRI) task to study the influence on content-related salience processing and expectedness. Salience was modulated for both sexual and non-sexual emotional photos in either expected or unexpected situations. Correlation between MRS and task fMRI was investigated by performing regression analyses controlling for age, gender, and gray matter content. Results/Conclusion: During picture processing, the extent of deactivation in the Posterior Cingulate Cortex (PCC) was attenuated by two different salience attributions: sexual content and unexpectedness of emotional content. Our results indicate that stimulus inherent salience induces an attenuation of the deactivation in PCC, which in turn is balanced by a higher level of glutamate in the dACC.